2018
DOI: 10.1166/jnn.2018.14556
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Photocatalytic Hydrogen Production of Pt-Graphene/TiO2 Composites from Water Splitting

Abstract: Hydrogen is considered as a promising energy source with its high energy yield, renewable, environment friendly properties. TiO2 modified with noble metal and nonmetal is widely used. In this study, Pt and graphene (GN) were used to modify TiO2 nanoparticles. GN/TiO2 (TG), Pt-TiO2 (PT), Pt-GN/TiO2 (PTG) was successfully synthesized by modified Hummers' method, alcohol thermal and photodeposition method, respectively. The characterizations of the synthesized catalysts by UV-vis/DRS, components analysis, XRD and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Incorporation of gold and graphene greatly increased hydrogen production in both the UV and visible regions of all the composites. The presence of co-catalysts such as Au and graphene improve the charge separation and suppresses the recombination of excited photogenerated carriers, resulting in a better evolution of H 2 [ 26 ]. Different studies [ 45 , 46 , 47 ] have demonstrated that when semiconductors, such as ZnO, are doped with noble metal or metal ions, they exhibit a negative shift in the Fermi level that implies a greater degree of electron accumulation in Au-loaded.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Incorporation of gold and graphene greatly increased hydrogen production in both the UV and visible regions of all the composites. The presence of co-catalysts such as Au and graphene improve the charge separation and suppresses the recombination of excited photogenerated carriers, resulting in a better evolution of H 2 [ 26 ]. Different studies [ 45 , 46 , 47 ] have demonstrated that when semiconductors, such as ZnO, are doped with noble metal or metal ions, they exhibit a negative shift in the Fermi level that implies a greater degree of electron accumulation in Au-loaded.…”
Section: Resultsmentioning
confidence: 99%
“…These improvements are in turn associated with a considerable enhancement of the electric near-field [ 45 ]. This activity relates strongly to the size and shape-dependent surface charge oscillation known as surface plasmon resonance (SPR) in the presence of light irradiation [ 26 ]. Furthermore, the incorporation of graphene on semiconductors creates the p–n junction, which also improves the separation of photogenerated charges [ 26 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations